Hubungan Pengetahuan dan Sikap terhadap Kejadian Anemia pada Remaja Putri di SMK YM Tahun 2024 - Syahrul Rudiansyah; Sulfiah, Wili; Anggraini, Lita; Ningsih, Selviana; Nurmaulina, Nasya (LPPM UNU CIREBON, 2025)
Anemia can cause various adverse effects for adolescent girls and wus (women of childbearing age = 15-49 years), including a weakened immune system, making patients more susceptible to infection, reduced physical and thinking abilities due to insufficient oxygen supply to the muscles and brain, and decreased academic achievement and work efficiency. This study aims to reveal various influences related to the occurrence of anemia in grade X and XI female students at SMK